METROLOGICAL CONTROL ANGLE MEASUREMENT ERRORS AND DISTANCE ELECTRONIC TOTAL STATIONS - Абдусали Самадович Суюнов; Анвар Абдисаидович Мирзаев; Шухрат Абдусалиевич Суюнов; Олим Абдигофурович Ураков (Open Academia, 2023)
METROLOGICAL CONTROL ANGLE MEASUREMENT ERRORS AND DISTANCE ELECTRONICTOTAL STATIONS